Program Peningkatan Pengetahuan dan Keterampilan Guru dalam Deteksi dan Intervensi Dini dalam Tumbuh Kembang Anak Sekolah Dasar melalui Penggunaan Flashcard Pediatrik dan Media Visual : di SD Inklusi Muhammadiyah 01 Candi Labschool UMSIDA - Arti, Widi; Widanti, Herista Novia; Wati, Tri Linggo (Universitas Nusantara PGRI Kediri, 2023)
Early detection is a process of testing and measurement conducted when the prevalence of diseases or disorders is high in the normal population. The aim of this community engagement program is to enhance the knowledge of teachers, shadows, and educators at SD Inklusi Muhammadiyah 01 Candi Labschool UMSIDA regarding early stimulation, detection, and intervention in the development of elementary school-aged children using pediatric flashcards as a tool. The methods used in the educational activities for teachers and educators include two-way lectures, demonstrations involving all teachers, as well as the provision of pediatric flashcards and assistance in creating visual learning media for teachers. A total of 31 individuals participated in this program, including 22 regular teachers, 8 shadow teachers, and 3 education personnel at SD Muhammadiyah 01 Candi Labschool UMSIDA, Sidoarjo Regency. The program commenced on March 3, 2023. Overall, it can be concluded that this community engagement program has successfully increased the knowledge and skills of teachers in visual learning methods for children with special needs and achieved a high level of satisfaction.